Effect of Health Education for Knowledge Pregnant Women's : Normal Delivery - Eugenia Carvalho De Araujo; Natalia Pereira; Etelvina Jose S. Tilman; Ana Claudia Da C. Guterres; Artur N. Corte Real Araujo (PT. Banjarese Pacific Indonesia, 2024)
This study aims to evaluate the effect of reproductive health education on pregnant women's knowledge about normal delivery. The research design used was qualitative with a literature study approach. Data were collected through the analysis of relevant literature on reproductive health education and pregnant women's knowledge of normal labor. The results of the analysis showed that the reproductive health education intervention significantly improved pregnant women's understanding of the labor process, including knowledge of the stages of labor, signs of labor, pain management, and postpartum care. Comparisons between the control and experimental groups also confirmed that the reproductive health education program was effective in improving the overall knowledge of pregnant women. These findings suggest that reproductive health education is an important strategy for optimally preparing pregnant women for childbirth. The implications of this study are the need for more structured and focused integration of reproductive health education in prenatal care, as well as the need for further research to understand the factors that influence the implementation and outcomes of reproductive health education programs.